Resource rents, human development and economic growth in Sudan - Elwasila Saeed Elamin Mohamed (Economies, 2020)
This study investigates the relationship between natural resource rents, human development and economic growth in Sudan using co-integration and vector error correction modelling (VECM) over the period 1970-2015. Institutions proved to play a role in determining a difference in whether a country is cured or blessed by resource abundance. In the case of Sudan, no time series data is available on institutional quality and is therefore excluded from the analysis. The role of institutions and macroeconomic policies is captured by other variables included in the empirical model. Co-integration tests confirm the existence of a long run equilibrium relationship between resource rents, human development and economic growth in Sudan. Empirical evidence from the estimated VECM shows that economic growth is positively affected by resource rents and development expenditure but surprisingly negatively affected by life expectancy at birth in the short run. In the long run, resource rents, school enrolment, life expectancy and financial development have negative significant effects on economic growth. Only development expenditure is found to affect economic growth positively. Resource rents are found to weaken education and health levels and this is indirectly channeled into negative effects of resource rents on economic growth. These results suggest that the government has been neglecting investments to build up human capital necessary for inclusive growth. Long run Granger causality tests show a unidirectional causal relationship running from resource rents to GDP growth as well as from development expenditure to GDP growth. School enrollment, life expectancy and financial development are found to be negatively Granger causing GDP growth. Long run causal relationships reconfirm that a resource curse exists indirectly mediated by weak human capital. The study recommends that the government should manage natural resource rents with a policy framework supporting creation of a virtuous economic circle between human development and economic growth. If pursued, this would promote sustained, inclusive and equitable growth in Sudan.
Keywords: 330; co-integration; development expenditure; economic growth; financial development; human development; resource rents; Sudan; VECM